2021
DOI: 10.1007/s10640-021-00581-x
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Emission Prices Over the Business Cycles

Abstract: We prove that under the most typical circumstances optimal emission prices are procyclical, i.e., prices should be lower during recessions. The procyclicality is more likely when emissions propagate very slowly into environmental damage. A prime example of such process is $$\hbox {CO}_2$$ CO 2 emissions. We show that carbon prices should be closely linked to the fluctuations of the marginal utility of consumption, which implie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 52 publications
(73 reference statements)
0
0
0
Order By: Relevance
“…Under the impact of the fossil fuel technology subsidy policy shock and the renewable energy technology subsidy policy shock, the government will increase subsidies to support energy technology innovation, and the total output, total consumption, and capital stock will also have a positive reflection. Heutel (2012) and Lintunen and Vilmi (2021) argued that carbon emissions are pro-cyclical under most environmental policies and that only optimal environmental policies can reduce the pro-cyclicality of carbon emissions to a certain extent. However, we can find that under the shocks of the fossil fuel technology subsidy policy and the renewable energy technology subsidy policy, pollutant emissions show a downward trend.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Under the impact of the fossil fuel technology subsidy policy shock and the renewable energy technology subsidy policy shock, the government will increase subsidies to support energy technology innovation, and the total output, total consumption, and capital stock will also have a positive reflection. Heutel (2012) and Lintunen and Vilmi (2021) argued that carbon emissions are pro-cyclical under most environmental policies and that only optimal environmental policies can reduce the pro-cyclicality of carbon emissions to a certain extent. However, we can find that under the shocks of the fossil fuel technology subsidy policy and the renewable energy technology subsidy policy, pollutant emissions show a downward trend.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Fischer and Springborn (2011) found that emissions intensity reduction targets significantly impact on economic growth more than caps or carbon taxes. Further studies, such as those by Fischer and Heutel (2013) and Lintunen and Vilmi (2021), explored the impacts of policies like carbon taxes and carbon pricing in different economic cycles. The NK framework enhances the RBC model by including market frictions, imperfect competition, and nominal rigidities.…”
mentioning
confidence: 99%